Angka Konsepsi Hasil Inseminasi Semen Cair Versus Semen Beku pada Kuda yang Disinkronisasi Estrus dan Ovulasi. - R I Afiriantini; B Purwantara; T L Yusuf; D Sajuthi; . Amrozi. (Media Peternakan, 2010)
Semen used for artificial insemination (AI) can be prepared in different ways, fresh extended fresh or chilled, or frozen-thawed (FT). The aim of the experiment was to evaluate the use of preserved semen to inseminate the oestrus mares. Nineteen mares were used in this research. The mares were synchronized with double injection of PGF2? 14 days apart. The follicle size was monitored using ultrasound scanner during the third day of oestrus, and 2500 IU hCG was administered at the same time. The AI was conducted 35 hours after hCG injection with total motile sperm 200x106 for chilled semen and 250-300x106 for frozen semen. The result demonstrated that the response of the oestrus with double injection of PGF2? was 73.7%. The conception rate (CR) was 14.3% (1/7) with frozen semen and 42.9% (3/7) with chilled semen. It is concluded that AI with chilled semen resulted higher conception rate than frozen semen.Key words: mare, synchronization, oestrus, ovulation, artificial insemination dose, conception rate